ENTREPRENEURSHIP IN CAR-FREE DAY - Irdiana, Sukma (Jurnal Entrepreneur dan Entrepreneurship, 2018)
This study aims to explore entrepreneurship in car-free day. Data were collected through interviews to 13 car-free day visitors as informants. The theme analysis (Creswell, 2009) was used to analyze the data. This research succeeded in exploring entrepreneurship in car-free day in the context of exploiting opportunity by selling merchandise required by the visitors. The visitors felt the social interaction during the car-free day. However, social interaction did not have an impact on entrepreneurship.